ANALISIS PERUBAHAN KEBIJAKAN INDONESIA TERHADAP ASEAN AGREEMENT ON TRANSBOUNDARY HAZE POLLUTION - Nugroho, Januar Aden; Putranti, Ika Riswanti (Journal of International Relations, 2018)
This study discusses Indonesian policy towards the AATHP agreement. Since the first AATHP haze agreement was formed in 2002, the Government of Indonesia has refused to ratify the agreement for almost 12 years. However, in 2014 a policy change occurred, with the Indonesian Government finally ratifying the agreement. This policy change raises the question, why Indonesia finally changed its policy towards AATHP. In explaining this research, the author uses the framework of liberalism theory to answer changes in Indonesian policy towards AATHP. Liberalism considers that this policy change is caused by the support of actors in Indonesian domestic politics. These actors in the form of private groups, interested actors and individual actors have become their own causes in Indonesia's policy changes to AATHP. Private groups, individual actors in domestic politics and interest groups are key actors in influencing how the Indonesian government takes its decisions on the AATHP agreement. In addition, support from ASEAN countries as well as the existence of domestic political turmoil were also the cause of the Indonesian Government finally changing its policy towards the AATHP agreement.